Chia (Salvia hispanica L) gel can be used as egg or oil replacer in cake formulations - Borneo Benista, Rafael (2010)
This study determined the overall acceptability, sensory characteristics, functional properties, and nutrient content of cakes made using chia (Salvia hispanica L) gel as a replacement for oil or eggs. Chia gel was used to replace 25%, 50%, and 75% of oil or eggs in a control cake formulation. Seventy-five untrained panelists participated in rating cakes on a seven-point hedonic scale. Analysis of variance conducted on the sensory characteristics and overall acceptability indicated a statistically significant effect when replacing oil or eggs for color, taste, texture, and overall acceptability (P<0.05). Post hoc analysis (using Fisher's least significant difference method) indicated that the 25% chia gel cakes were not significantly different from the control for color, taste, texture, and overall acceptability. The 50% oil substituted (with chia gel) cake, compared to control, had 36 fewer kilocalories and 4 g less fat per 100-g portion. Cake weight was not affected by chia gel in the formulation, although cake volume was lower as the percentage of substitution increased. Symmetry was generally not affected. This study demonstrates that chia gel can replace as much as 25% of oil or eggs in cakes while yielding a more nutritious product with acceptable sensory characteristics. © 2010 American Dietetic Association.